Effects of health literacy promotion program on obesity prevention behaviors and the body weight of school-age children with overnutrition - Kowkom, Prapaphan; Sananreangsak, Siriyupa; Sarapat, Photjanart (NU Journal of Nursing and Health Sciences, 2024)
This research was quasi-experimental, two groups pretest-posttest design. The objective aimed to examine the effects of the health literacy promoting program on obesity prevention behaviors and the body weight of school-age children with overnutrition. The samples included 40 school-age children with overnutrition for grades 4-6 in primary schools. They met the inclusion criterion and randomly assigned to the experimental (n=20) and control group (n=20). Data were collected from November 2022 to January 2023. The experimental group received the health literacy promoting program, which was developed following health literacy The program comprised of 6 steps: 1) Access to health information; 2) Understanding of health; 3) Interaction, interrogation and exchange of health information; 4) Behavioral decision-making; 5) Behavior practices; and 6) Further instruction to behavioral practices, while the control group received regularly teaching in school. Research instruments consisted of the obesity prevention behaviors questionnaire, which had a Cronbach’s alpha of .80. Data were analyzed using descriptive statistics and independent t-test.The results revealed that after receiving the program, the experimental group had the mean scores of obesity prevention behaviors significantly higher than the control group (t38 = 6.81, p <.001 and t38 = 2.12, p = .04 ) and the mean of in the body weight were not differences.The results suggest that nurses and caregivers of school-age children could apply the health literacy promotion program to encourage appropriate dietary and physical activity behaviors for school-age children.